Konsep Hak Asasi Manusia dalam Beragama Perspektif Al-Quran: Analisis Surah Al-Baqarah Ayat 256 Penafsiran Wahbah Az-Zuhaili dalam Tafsir Al-Munir - Halim, Abdul; Sahrin, Abu; Ardiansyah, Febri (Lembaga Yasin AlSys, 2023)
This research aims to analyze the construction of the interpretation of Wahbah al-Zuhaili in the Al-Qur'an surah Al-Baqarah verse 256 related to human rights in religion. And the implementation of the concept of religious freedom in the present. The method used in this research is a qualitative method with the type of library research. This research will use a Sociology of Religion approach which seeks to explore more deeply how to understand socio-religious phenomena in social life currently faced, namely related to Human Rights in Religion. The research results show that Imam Wahbah al-Zuhaili's interpretation in interpreting Surah Al-Baqarah Verse 256 regarding freedom of religion has a very clear explanation, namely that it is not permissible for anyone to force someone to adhere to the Islamic religion. In terms of interpreting these verses on freedom of religion, Sheikh Wahbah Az-Zuhaili tends to use the method of interpreting verses bil verses, namely interpreting one verse with another verse of the Qur'an. Freedom of religion in the Indonesian context is actually legally and formally guaranteed by The 1945 Constitution, especially articles 28E, 28I, and 29. Restrictions on freedom can only be carried out through law as regulated in Article 28J of the 1945 Constitution. Law Number 39 of 1999 concerning Human Rights also regulates human rights and basic human obligations. Article 22 of Law Number 39 of 1999. However, the facts on the ground are that actions and actions are often found that lead to restrictions and closing down religious freedom. Among several factors that cause anti-religious freedom are high levels of intolerance, radicalism and violence.